Swipes and Saves: A Taxonomy of Factors Influencing Aesthetic Assessments and Perceived Beauty of Mobile Phone Photographs - Leder, Helmut; Hakala, Jussi; Peltoketo, Veli-Tapani; Valuch, Christian; Pelowski, Matthew (Frontiers in Psychology, 2022)
Digital images taken by mobile phones are the most frequent class of images created today. Due to their omnipresence and the many ways they are encountered, they require a specific focus in research. However, to date there is no systematic compilation of the various factors that may determine our evaluations of such images, and thus no explanation of how users select and identify relatively 'better' or 'worse' photos. Here, we propose a theoretical taxonomy of factors influencing the aesthetic appeal of mobile phone photographs. Beyond addressing relatively basic/universal image characteristics, perhaps more related to fast (bottom-up) perceptual processing of an image, we also consider factors involved in the slower (top-down) re-appraisal or deepened aesthetic appreciation of an image. We span this taxonomy across specific types of picture genres commonly taken—portraits of other people, selfies, scenes; food. We also discuss the variety of goals, uses, and contextual aspects of users of mobile phone photography. As a working hypothesis, we propose that two main decisions are often made with mobile phone photographs: (1) Users assess images at a first glance—think swiping through a stack of images —focusing on visual aspects that might be decisive to classify them from 'low quality' (too dark, out of focus) to 'acceptable' to, in rare cases, 'an exceptionally beautiful picture'. (2) Users make more deliberate decisions regarding one’s ‘favorite’ picture or the desire to preserve or share a picture with others, which are presumably tied to aspects such as content, framing, but also culture or personality, which have largely been overlooked in empirical research on perception of photographs. In sum, the present review provides an overview of current focal areas and gaps in research and offers a working foundation for upcoming research on the perception of mobile phone photographs as well as future developments in the fields of image recording and sharing technology.